1998
DOI: 10.1084/jem.187.9.1417
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphotyrosine Phosphatase SHP-2 Participates in a Multimeric Signaling Complex and Regulates T Cell Receptor (TCR) coupling to the Ras/Mitogen-activated Protein Kinase (MAPK) Pathway in Jurkat T Cells

Abstract: Src homology 2 (SH2) domain–containing phosphotyrosine phosphatases (SHPs) are increasingly being shown to play critical roles in protein tyrosine kinase–mediated signaling pathways. The role of SHP-1 as a negative regulator of T cell receptor (TCR) signaling has been established. To further explore the function of the other member of this family, SHP-2, in TCR-mediated events, a catalytically inactive mutant SHP-2 was expressed under an inducible promoter in Jurkat T cells. Expression of the mutant phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 46 publications
10
88
1
Order By: Relevance
“…We also present data showing indications that the negative signals transmitted by the adapter-like function of SHP-2 could be mediated via interaction with the ubiquitin ligases of the Cbl family. Earlier work with Jurkat cells transfected with SHP-2 C>S showed that over-expression of catalytic inactive SHP-2 isoforms resulted in reduced TCR-mediated activation of ERK in bulk cultures [18]. Here we extend the finding that SHP-2 C>S leads to impaired activation of ERK also in individual, primary T lymphocytes ( Fig.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…We also present data showing indications that the negative signals transmitted by the adapter-like function of SHP-2 could be mediated via interaction with the ubiquitin ligases of the Cbl family. Earlier work with Jurkat cells transfected with SHP-2 C>S showed that over-expression of catalytic inactive SHP-2 isoforms resulted in reduced TCR-mediated activation of ERK in bulk cultures [18]. Here we extend the finding that SHP-2 C>S leads to impaired activation of ERK also in individual, primary T lymphocytes ( Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore the catalytic activity is crucial for the TCR-induced activation of ERK1/2. These results achieved in primary T lymphocytes extend the finding of Frearson and Alexander [18], who used Jurkat lymphoma cells. In addition, when analyzing the activation status of T lymphocytes on the basis of the expression of activation-induced receptors CD96, CD25 and CD71 on the cell surface 6, 24 and 48 h after Ag-mediated restimulation, there was no difference in the activation status of cells expressing the different isoforms of SHP-2 ( Fig.…”
Section: Activation and Proliferation Are Intact In Individual T Lympsupporting
confidence: 88%
See 3 more Smart Citations